The Islamic soukoukes prospects and challenges - Seghir, Nadjia (Journal of Human Sciences, 2022)
The interest to Islamic soukoukes is since the end of the eighties, the group of international Islamic doctrine is the first to show a big interest and to make a decision concerning them, called mortgage bonds and investment bonds . After that, searches have been carried in this context, to be finally gathered under the name of Islamic soukoukes or soukoukes of legal investment, like some persons call them to avoid denomination ideology. They knew a big expansion and they are more and more required, in the framework of a worldwide orientation towards economy morality, or as we call it, the investment based on Islamic soukoukes that exclude usury, misappropriation and infringement to people’s money. Their use domains are various, and have an increasing importance; they are used as financing tools through financial markets in some countries, nevertheless, encounter some challenges and obstacles in other countries such as Algeria, in the absence of a legislative framework that supports its legal side to complete the Islamic exchan and so that the soukoukes will be the second pavilion of financial titles market next to shares.